(untitled) (Public Sector Economics - submission site, 2022)
I use household survey data to microsimulate the impact of the COVID-19 crisis on income distribution in Spain. I estimate the cost of potential lockdowns under three different low-income public protection schemes. Results show that although the COVID-19 shock has reduced income for all deciles of the income distribution, the losses are not uniformly distributed. The worst economic effects of the pandemic are not on the poorest, but on individuals in the middle and wealthy groups of the ex-ante income distribution. Low-income benefits help to moderate income losses and to curb poverty and inequality at various levels. It might be necessary to raise taxes and to resort to expenditure reducing policies to maintain protection in the context of contraction and lower government revenues.